Morphological and chemical characterization of Ultisols with darkened subsurface horizons in Santa Catarina state - Lunardi Neto, Antônio; Almeida, Jaime Antonio de (Revista de Ciências Agroveterinárias, 2013)
In the state of Santa Catarina Argissolos occur with subsurface horizons darkened similar to sombric horizons described in Soil Taxonomy and the World Reference Base for Soil Resources (WRB) These soils are very poorly studied as their occurrence is not so significant in relation to other soils. This is due to the difficulties inherent in research of the genesis of such horizons, which are often complex. Nevertheless, such soils occupy significant areas in the state, and are worthy of further research with respect to chemical, physical and mineralogical properties. Such soils are used in agriculture, forestry and pasture. To this end, we selected three profiles of Ultisols, situated in the municipalities of Içara, Rancho Queimado and Alfredo Wagner, red, yellow and grayish-brown Ultisols, respectively. Then we proceeded to the morphological description. Sample structures were collected for chemical analysis. The chemical data indicated soils with acid reaction and desaturation. The results also showed that the soils exhibit morphological data that indicate the possibility of illuviation of organic matter especially in the red Ultisol. The results also showed the existence of 2:1 clay minerals with hydroxyl-aluminum in interlayers in all Ultisols.